KOMPARASI MAHARAH KITABAH DENGAN METODE IMLA’ ANTARA SISWA ALUMNI MTS DAN SMP DI KELAS XI MAN 2 BANDAR LAMPUNG - Zilvi Khairunnisa; Yeni Lailatul Wahidah; Afif Amrullah; Safari Daud (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to compare the Arabic writing skill (maharah kitabah) using the imla’ method between students from MTs and SMP backgrounds in grade XI A1 of MAN 2 Bandar Lampung. This quantitative comparative research involved 28 students selected through purposive sampling, consisting of 14 MTs alumni and 14 SMP alumni. Data were collected through observation, interviews, documentation, and a written imla’ test. The results of the Shapiro–Wilk test show that the data from both groups are normally distributed, and the Independent Sample t-Test revealed that the average score of SMP alumni was higher than that of MTs alumni; however, the difference was not statistically significant (p = 0.207 > 0.05). These findings indicate that prior educational background does not significantly influence students’ Arabic writing ability at the MA level. The learning process at MAN 2 Bandar Lampung appears to equalize students' abilities regardless of their previous schooling, suggesting that teaching strategies should focus on strengthening writing skills across groups.